Pendampingan Hukum Pro Bono dan Peranannya dalam Meningkatkan Kepercayaan Publik terhadap Sistem Hukum - Rahmanisa Zahra, Maysanda; Sakti, Reza Yuda; Ardiyanti, Dinita; Adnan Ramadhan, Muhammad Rifki; An Naufal, Yazid (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Pro bono legal assistance has become an interesting focus amidst the challenges of a legal system that is often considered far from the reach of the general public. This article examines the strategic role of free legal assistance by advocates in building a bridge of public trust in a legal system that is often seen as elitist and expensive. With an empirical approach, this study explores how pro bono services not only provide access to justice for vulnerable groups, but also create a domino effect: improving the image of the law in the eyes of the public. Data collected through interviews with legal practitioners and analysis of real cases, show that this assistance is able to erode negative stigma and prove that the law can side with the weak. This article offers a fresh perspective that pro bono is not just charity, but a social investment for a more humane and trustworthy legal system.